2021
DOI: 10.3390/antiox10091463
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 and Heme Oxygenase-1 Involvement in Atherosclerosis Related Oxidative Stress

Abstract: Atherosclerosis remains the underlying process responsible for cardiovascular diseases and the high mortality rates associated. This chronic inflammatory disease progresses with the formation of occlusive atherosclerotic plaques over the inner walls of vascular vessels, with oxidative stress being an important element of this pathology. Oxidation of low-density lipoproteins (ox-LDL) induces endothelial dysfunction, foam cell activation, and inflammatory response, resulting in the formation of fatty streaks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 175 publications
(303 reference statements)
1
47
0
Order By: Relevance
“…A large number of studies have described the involvement of the Nrf2 antioxidant system in the prevention or attenuation of age-related diseases including atherosclerosis, vascular calcification, cataract formation, and macular degeneration [ 21 , 25 , 33 , 46 , 47 , 48 ]. There are numerous clinical trials targeting the Nrf2 system in diverse clinical conditions including cancer, chronic kidney disease, diabetes, aging problems, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have described the involvement of the Nrf2 antioxidant system in the prevention or attenuation of age-related diseases including atherosclerosis, vascular calcification, cataract formation, and macular degeneration [ 21 , 25 , 33 , 46 , 47 , 48 ]. There are numerous clinical trials targeting the Nrf2 system in diverse clinical conditions including cancer, chronic kidney disease, diabetes, aging problems, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, hyperglycemia-induced ROS accumulation and hyperglycemia cause endothelial cell apoptosis and inflammation, resulting in endothelial injury (reviewed in [ 6 ]). The pathogenesis of atherosclerosis includes oxidative stress, high levels of oxidized lipoproteins, immune reactivity, and inflammation, as well (reviewed in [ 3 , 7 , 8 ]). Importantly, vascular endothelial dysfunction caused by dyslipidemia is considered the main factor for the beginning of atherosclerosis (reviewed in [ 8 , 9 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of atherosclerosis includes oxidative stress, high levels of oxidized lipoproteins, immune reactivity, and inflammation, as well (reviewed in [ 3 , 7 , 8 ]). Importantly, vascular endothelial dysfunction caused by dyslipidemia is considered the main factor for the beginning of atherosclerosis (reviewed in [ 8 , 9 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pharmacological activation of Nrf2 suppresses endothelial pyroptosis by reducing the overproduction of ROS ( 16 ). It is reported that Nrf2 may be an ideal therapeutic target for prevention of diabetic atherosclerosis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%